ОN THE NEED OF REGULATING SURROGACY: RECENT CASE LAW AND ACTIVITIES IN 2014 - Bordaš, Bernadet (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The paper discusses three important events for а future possible international instrument on surrogacy with cross-border effects. The Hague Conference document “The desirability and feasibility of further work on the Parentage / Surrogacy Project”, the first two judgments of the European Court of Human Rights on the effects of cross-border surrogate motherhood and two judgments of the Court of the European Union on the right of intended mothers to maternity leave suggest that international regulation of the issues is desirable, but large differences between internal laws of states require further study on the possibility of reaching a consensus to draw up and accept a binding or not-binding multilateral instrument on the subject matter. The Mennesson v France ECHR judgment is particularly important, because it establishes violation of the right to respect private life of children who were given birth by a surrogate mother, and creates by this a contradiction between the margin of appreciation of a respective State and the principle of best interests of the child.